Parcours de professeurs des écoles débutants : du choix du métier au premier poste. Retours sur une construction identitaire et professionnelle - Thierry Bouchetal (Recherches en Éducation)
From the results of an investigation with 1st year recruited primary school teachers, we first tried to determine what made their project to teach, in order to understand better what changes occur when facing School and teacher-training reality. Exploring the trying nature of the entry in a job yet assumed to be known, we notice that novice primary-school teachers, define a demanding professional and educational project, taking support on rich personal experiences which they mobilise for their first posts. The school they encounter is much more fragmented than what they had perceived in the training and their first posts are usually implemented in more difficult contexts than the ones they had experienced, that gives them new resources but also questions on their professional identity. While trying to answer the question of professional development for first degree novice teachers, the research shows that taking up this job means experiencing adjustment process, and constantly going past first concepts.